Optimasi Pembuatan Film Biodegradabel dari Komposit Pati Sagu – MCC yang Dimodifikasi dengan Asam Sitrat - Trisuciati Syahwardini; Bahruddin; Ida Zahrina (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2020)
Optimization is a way to find variable values that are considered optimal, effective, and efficient to achieve the desired results. The approach that is more often used for optimization problems with multi-variables is the desirability function. The components carried out by the optimization are microcrystalline cellulose (MCC) (x1), citric acid (x2), sorbitol (x3) with the response are Tensile Strength (Y1), Elongation (Y2), Modulus young (Y3), Biodegradability (Y4), and Water Uptake (Y5). Optimization is done by using Design Expert 10.0.1 Software. Through Desirability Function analysis, the optimum treatment composition was obtained at the MCC filler variation of 18% w / w starch, citric acid 3% w / w starch, and sorbitol 33% w / w starch with the optimum response value predicted for tensile strength (Y1) = 11.38 MPa; Elongation (Y2) = 13.54%; Young's modulus (Y3) = 118.05 MPa; Biodegradability (Y4) = 46.89%; and Water Uptake (Y5) = 52.13%. The combined desirability value is 0.551